2005
DOI: 10.3200/genp.132.4.446-461
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Metacognitive Responsiveness: Cognitive and Personality Correlates

Abstract: Individuals differ not only in the ability to make decisions, but also in the degree to which they respond adaptively to uncertainty about those decisions. We examined how optimally 124 participants used an uncertain response on near-threshold trials of a psychophysical task. All participants showed overconfidence, but women tended to be more adaptive than men in responsiveness to uncertainty. Participants who responded to uncertainty most optimally exhibited more cognitive failures, fewer attention deficit an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 30 publications
4
20
0
1
Order By: Relevance
“…It does not matter if observers overestimate or underestimate their probability of success, because we require them to make comparative judgments. We expect an objective task such as the one used here to measure more robust effects than the ones obtained from confidence ratings, which are subject to uncontrollable variability between observers and over time (20,25). We set up a task that is drastically simple-from the observer's point of view-compared with most decision-making tasks.…”
Section: Discussionmentioning
confidence: 99%
“…It does not matter if observers overestimate or underestimate their probability of success, because we require them to make comparative judgments. We expect an objective task such as the one used here to measure more robust effects than the ones obtained from confidence ratings, which are subject to uncontrollable variability between observers and over time (20,25). We set up a task that is drastically simple-from the observer's point of view-compared with most decision-making tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Результаты выполнения методики ASAP проявились и в из-менении СК. Как и в предыдущем исследовании, успеш-ность выполнения задания была напрямую связана с пока-зателями СК в обоих полушариях -они были выше при бо-лее успешном результате [41].…”
Section: о б з о р ыunclassified
“…Women are more willing than men to adopt a fashion innovation earlier than other consumers-a risky consumer behavior (Workman & Cho, 2012) and are more likely than men to purchase products impulsively (Chen, 2001). Other research (that did not examine risk related to purchasing apparel) found that women (compared with men) are more open to uncertain and unstructured contexts (Maio & Esses, 2001;Washburn, Smith, & Taglialatela, 2005), are disinclined to take risks (e.g., Wagner, 2001) or that men and women did not differ in tendency for risk taking (e.g., Maxfield et al 2010). Research has found that women score higher than men on brand sensitivity (Beaudoin & Lachance, 2006;Warrington & Shim, 2000) and brand consciousness (Workman & Lee, 2013).…”
Section: Gender and Consumer Behaviourmentioning
confidence: 99%